Synaptic plasticity in fronto-insular circuits underlying stress susceptibility and resilience - Devin Rocks; Conor Liston (Neuroscience Research)
Chronic stress may trigger depressive episodes in vulnerable individuals but the underlying mechanisms remain incompletely understood. Converging lines of evidence indicate that these mechanisms may converge on the dysregulation of synaptic transmission in the anterior cingulate and anterior insula, disrupting motivation and hedonic function. In this review, we examine how chronic stress and antidepressants modulate synaptic connectivity in stress-sensitive brain circuits. We discuss the roles of various synaptic and molecular pathways in these processes, their interaction with circadian rhythms, and their contributions to the regulation of mood, with a particular focus on anhedonia. In the short term, stress effects on neuronal activity may be adaptive, but repeated engagement of these adaptations may lead to circuit dysfunction—a phenomenon known as allostatic load. We also highlight new insights from neuroimaging studies that suggest that synaptic reorganization within fronto-insular circuits that process valence, salience, and motivation could play a critical role in driving risk for depression and transitioning between mood states. We propose a working model in which synapse loss in the anterior cingulate and anterior insula may contribute to depression by disrupting effort valuation computations, which regulate decision making and hedonic function by integrating information about anticipated rewards and the effort required to obtain them.